2019
DOI: 10.1038/s41418-018-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the SAP18/HDAC1 complex by targeting TRIM56 and Nanog is essential for oncogenic viral FLICE-inhibitory protein-induced acetylation of p65/RelA, NF-κB activation, and promotion of cell invasion and angiogenesis

Abstract: Kaposi's sarcoma (KS), a highly invasive and angiogenic tumor of endothelial spindle-shaped cells, is the most common AIDS-associated cancer caused by KS-associated herpesvirus (KSHV) infection. KSHV-encoded viral FLICE-inhibitory protein (vFLIP) is a viral oncogenic protein, but its role in the dissemination and angiogenesis of KSHV-induced cancers remains unknown. Here, we report that vFLIP facilitates cell migration, invasion, and angiogenesis by downregulating the SAP18-HDAC1 complex. vFLIP degrades SAP18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…EZ-Magna ChIP A/G Chromatin Immunoprecipitation Kit (Merck, Darmstadt, Germany) was used for ChIP analysis as previously described [76]. Cells (10 7 ) cross-linked by 1% formaldehyde were harvested to suffer sonication.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…EZ-Magna ChIP A/G Chromatin Immunoprecipitation Kit (Merck, Darmstadt, Germany) was used for ChIP analysis as previously described [76]. Cells (10 7 ) cross-linked by 1% formaldehyde were harvested to suffer sonication.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…The photomultiplier tube voltage was set as 300 to 350 V and the resolution as 50 μm. Target bands were excised and subjected to LC-electrospray ionization MS/MS analysis by Q Exactive as previously established (Shanghai Applied Protein Technology Co. Ltd.) ( 33 ). Samples with or without ACA were also incubated with DyLight 488–Phosphine to act as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, vFLIP can directly interact with IκB kinase (IKK) α, IKKβ, and IKKγ/ NF-κB essential modulator (NEMO) complexes, promoting IκBα destruction and thus NF-κB activation (Field et al, 2003; Guasparri et al, 2004). Additionally, it was recently demonstrated that vFLIP uses an alternative pathway to induce the activation of NF-κB by promoting the degradation of the histone deacetylase complex components SAP-18 and histone deacetylase (HDAC) 1, which target p65 for deacetylation (Ding et al, 2019). Importantly, activation of NF-κB is essential for vFLIP-induced endothelial cell migration, invasion, and angiogenesis (Ding et al, 2019).…”
Section: Kaposi’s Sarcoma-associated Herpesvirusmentioning
confidence: 99%
“…Additionally, it was recently demonstrated that vFLIP uses an alternative pathway to induce the activation of NF-κB by promoting the degradation of the histone deacetylase complex components SAP-18 and histone deacetylase (HDAC) 1, which target p65 for deacetylation (Ding et al, 2019). Importantly, activation of NF-κB is essential for vFLIP-induced endothelial cell migration, invasion, and angiogenesis (Ding et al, 2019). In an NF-κB-dependent manner, and in coordination with LANA, vFLIP increases expression of the epigenetic modifier EZH2, which in turn modulates the pro-angiogenic factor Ephrin-B2 (He et al, 2012).…”
Section: Kaposi’s Sarcoma-associated Herpesvirusmentioning
confidence: 99%